DECONSTRUCTING THE IDEOLOGY OF RESISTANCE SHOWN BY THE PEOPLE LIVING AT CANDIKUNING VILLAGE TO THE MANAGEMENT OF EKA KARYA BALI BOTANICAL GARDEN - Sujana, I Wayan; Wirawan, AA Bagus; Sirtha, I Nyoman; Dhana, I Nyoman (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies), 2016)
The people living at Candikuning Village are not involved in the management of the Eka Karya Bali Botanical Garden; however, they intend to enjoy the retribution which is received by the Botanical Garden, for which they show their resistance to the management. This article is intended to understand the ideology which has inspired the local people to argue that they are entitled to the retribution received by the Eka Karya Bali Botanical Garden. The data were collected through in-depth interview, observation, and documentation techniques. The data were critically analyzed using the deconstruction method. Based on the analysis of the facts which had inspired the resistance shown by the local people living at Candi Kuning Village to the management of the Bali Eka Karya Botanical Garden, it could be understood that the geopolitical ideology was used as the basis of the resistance. Therefore, the management of the Bali Eka Karya Botanical Garden should give some of the retribution they received to the local people. The Botanical garden is located at Candikuning Village or part of the area of Candikuning Village. However, the village had never received any retribution from the Botanical Garden. The management should remember the proverb “di mana bumi dipijak di situ langit dijunjung” (we should adjust ourselves to the environment where we stay), based on the philosophy of Tri Hita Karana, meaning that the management should give retribution to the temple located at the area of the Botanical Garden.